Les signes expressifs corporels de la conversation par vidéoconférence - Christophe Bouyssi; Pascal Marquet (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This article examines online intercultural exchanges as a double-space framework composed of face-to-face and remote classrooms. Our research focuses on the way learners of French as a foreign language use group-based videoconferencing to coordinate their conversations with a group of target-language speakers. Combining conversationalist approaches (Goffman, Traverso, Cicurel), we consider conversation as both a polylog and a social and didactic activity. The study analyses the non-verbal, proxemic and gestural aspects of the interactions, in order to better understand their dynamics. The analysis demonstrates that student engagement enables the classroom to become a dynamic learning space where active exchange is cadenced both by collaboration and competition.